Studies on the crystallization behavior of nylon-6 in the presence of layered silicates using variable temperature WAXS and FTIR - Nair, S. S.; Ramesh, C. (Macromolecules, 2005)
The crystallization of nylon-6 clay nanocomposite was studied by variable temperature wide-angle X-ray scattering (WAXS) and Fourier transform infrared spectroscopy (FTIR). Nylon-6 was found to crystallize into gamma phase at 210 degreesC, as indicated by its characteristic peaks in WAXS. However, an additional peak was observed close but on the lower angle side of the main gamma phase peak, indicating the presence of a metastable phase. The extent of metastable phase that developed was dictated by the clay content in the nanocomposite as well as the crystallization conditions. The temperature dependence of the d spacing of the gamma phase obtained in the presence of clay layers showed difference from the gamma phase obtained by treating nylon-6 in KI/I-2 solution. Variable temperature FTIR studies were conducted on the gamma phases for the first time, and it showed definite differences in the spectra of the phases obtained by the two methods.

Synthesis and characterization of main chain thermotropic liquid crystalline polyesters based on methyl 4-[4 `-(omega-hydroxyalkoxy)blphenyl-4-yl]-4-oxobutyrate: Effects of keto group and connectivity on mesophasic characteristics of biphenyl based AB-typ - Ranganathan, T.; Ramesh, C. (Reactive & Functional Polymers, 2006)
A series of biphenyl based main chain thermotropic liquid crystalline polyesters, poly(hydroxyalkoxybiphenyl oxobutyrate) [PRBOB-2,n (n = 2-8)], containing various methylene spacers was synthesized by using the novel AB-type self-polycondensation route from the monomers, methyl 4-[4'-(omega-hydroxyalkoxy)biphenyl-4-yl]-4-oxobutyrate (HBOB-2,n). The mesophase characteristics of these polyesters was studied using DSC, polarized light optical microscopy and XRD techniques. The transition temperatures were found to decrease upon increasing the spacer length with an even polymer exhibiting higher transition temperature than the odd counterpart. The mesophase type also indicated an odd-even oscillation with the even members showing normal smectic phase and odd members exhibiting tilted smectic phase. The comparison of mesophasic characteristics of these polyesters with that of structurally similar AB-type polyesters indicated that the total number of atoms connecting the mesogen in a polymeric repeat unit governs the nature of the mesophase while the rigidity of the system dictates the magnitude of transition temperatures. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: AB approach; biphenyl mesogen; effect of connectivity; Liquid crystalline polyesters

Structural phase transitions of syndiotactic polystyrene - Gowd, E. Bhoje; Tashiro, Kohji; Ramesh, C. (Progress in Polymer Science, 2009)
Syndiotactic polystyrene (sPS) exhibits four crystal modifications (alpha, beta, gamma, and delta), along with intermediate forms with different molecular conformations, as well as different chain-packing structures. The extensive literature on the crystal structures exhibited by sPS is reviewed herein, including, the mechanisms of phenomena such as solvent-induced crystallization, thermally induced crystallization and gelation, and the phase transitions among the various crystalline forms. The latter have been studied by static and dynamic wide-angle and small-angle X-ray scattering, infrared and Raman spectra, and neutron scattering, etc., in addition to computer simulations. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: crystal structure; Gelation; phase transition; polymorphism; Solvent-induced crystallization; Syndiotactic polystyrene

Structure-property relationship of different types of polyester industrial yarns - Samui, Barun Kumar; Prakasan, Manikanda Priya; Ramesh, C.; Chakrabarty, Debabrata; Mukhopadhyay, R. (Journal of the Textile Institute, 2013)
Four major types of polyester industrial yarns (1000 Denier) which are used commercially were studied for their key structural parameters. An attempt has been made to establish a relationship between morphology and properties of these yarns. High tenacity (HT) polyester yarn has the highest birefringence, amorphous orientation, and long period but is relatively less crystalline. High shrinkage characteristic of HT polyester yarn can be accounted for its higher amorphous orientation. High modulus low shrinkage (HMLS) polyester yarn has higher crystallinity and crystal size compared to HT yarn. Fraction of tie molecules of these yarns has been calculated and found that low shrinkage (LS) and super low shrinkage (SLS) yarns have lesser tie molecules. These LS and SLS yarns are tailor-made to achieve lower shrinkage and at the same time maintaining a good level of tenacity. This is achieved with lower amorphous orientation in the final drawn yarn structure. Amorphous orientation was found to have stronger influence than any other structural parameter on the key yarn properties like modulus, tenacity, elongation, and shrinkage.
Keywords: modulus; orientation; polyester; shrinkage; structure

Studies on the static and dynamic properties of different types of polyester industrial yarns - Samui, Barun Kumar; Dasgupta, Saikat; Mukhopadhyay, R.; Ramesh, C.; Chakrabarty, Debabrata (Journal of the Textile Institute, 2016)
Four major types of polyester industrial yarns, viz. high tenacity (HT), high modulus low shrinkage (HMLS), low shrinkage (LS) and super low shrinkage (SLS) polyester yarns, were studied for their static and dynamic properties. An attempt has been made to establish a linkage between static and dynamic properties of these yarns with its structure and with its end applications. HMLS and HT polyester yarns have lower tan delta and work loss, which are the desired characteristics required for its end applications which include tire and conveyer belt. Higher overall orientation and higher fraction of tie molecules helped to achieve these properties in HT and HMLS polyester yarns. LS and SLS polyester yarns are mostly used for static applications. Low thermal shrinkage is the key requirement for the downstream processes of these yarns. Lower amorphous orientation in these two yarns is primarily responsible for achieving very low thermal shrinkage. A good co-relation has been established between the peak temperature of work loss (in slow speed hysteresis test) and the peak temperature of tan delta (in high-speed dynamic test).
Keywords: creep; modulus; polyester; shrinkage; tan delta; work loss